2020
DOI: 10.1016/j.ijid.2019.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating hepatitis B virus immune escape and polymerase mutants among HBV-positive patients attending Institut Pasteur de Bangui, Central African Republic

Abstract: HighlightsThe region spanning surface antigen and polymerase genes was sequenced in 51 out of 118 HBsAg positive patients in the Central African Republic.Three potentials HBV Immune Escape Mutants sY100C, sA128V, sM133T as well as several polymerase mutants were detected.HBV genotypes E were dominant (96%) compared to subgenotype A1 (4%).Serotype ayw4 accounted for genotype E and ayw1 accounted for subgenotype A1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Other mutations with clinical significance were sY100S, sK122R, sM197T, sW201*, sS204R and sS204N which impair the production and secretion of HBsAg, associated with low HBV viral load and OBI [ 25 , 26 , 27 , 28 , 29 , 34 , 35 , 37 ]. In the polymerase region, the most common mutations were rtS109P, rtM129L and rtV163I found in seven participants each similar to other studies which reported these mutations in genotype A and indeed these mutations were present in genotype A in this study [ 49 , 50 , 51 ]. These three mutations appeared together in six genotype A participants; rtS109P was also found in genotype E. We report no classic drug resistance-associated mutations such as rtL80I/V, rtV173L, rtL180M, rtA181S, rtA194T, rtS202I, rtM204V/I, rtN236T and rtM250L/V associated with resistance against lamivudine, telbivudine, adefovir, entecavir and tenofovir in this study similar to other studies [ 21 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other mutations with clinical significance were sY100S, sK122R, sM197T, sW201*, sS204R and sS204N which impair the production and secretion of HBsAg, associated with low HBV viral load and OBI [ 25 , 26 , 27 , 28 , 29 , 34 , 35 , 37 ]. In the polymerase region, the most common mutations were rtS109P, rtM129L and rtV163I found in seven participants each similar to other studies which reported these mutations in genotype A and indeed these mutations were present in genotype A in this study [ 49 , 50 , 51 ]. These three mutations appeared together in six genotype A participants; rtS109P was also found in genotype E. We report no classic drug resistance-associated mutations such as rtL80I/V, rtV173L, rtL180M, rtA181S, rtA194T, rtS202I, rtM204V/I, rtN236T and rtM250L/V associated with resistance against lamivudine, telbivudine, adefovir, entecavir and tenofovir in this study similar to other studies [ 21 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the polymerase region, the most common mutations were rtS109P, rtM129L and rtV163I found in seven participants each similar to other studies which reported these mutations in genotype A and indeed these mutations were present in genotype A in this study [ 49 , 50 , 51 ]. These three mutations appeared together in six genotype A participants; rtS109P was also found in genotype E. We report no classic drug resistance-associated mutations such as rtL80I/V, rtV173L, rtL180M, rtA181S, rtA194T, rtS202I, rtM204V/I, rtN236T and rtM250L/V associated with resistance against lamivudine, telbivudine, adefovir, entecavir and tenofovir in this study similar to other studies [ 21 , 51 , 52 ]. The rtY135S mutation was mostly seen in the treatment of non-responders and some studies classified it under drug resistance mutations against lamivudine, telbivudine, adefovir and entecavir but its characterization is not yet concluded [ 53 , 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the polymerase region, the most common mutations were rtS109P, rtM129L and rtV163I found in 7 participants each similar to other studies which reported these mutations in genotype A and indeed these mutations were present in genotype A in this study [50][51][52]. These 3 mutations appeared together in 6 genotype A participants, rtS109P was also found in genotype E. We report no classic drug resistance-associated mutations such as rtL80I/V, rtV173L, rtL180M, rtA181S, rtA194T, rtS202I, rtM204V/I, rtN236T and rtM250L/V associated with resistance against lamivudine, telbivudine, adefovir, entecavir and tenofovir in this study similar to other studies [22,52,53]. The rtY135S mutation was mostly seen in treatment non-responders and some studies classified it under drug resistance mutations against lamivudine, telbivudine, adefovir and entecavir but its characterization is not yet concluded [54][55][56][57].…”
Section: Discussionmentioning
confidence: 49%
“…Two additional genotypes I and J were recently proposed [27]. In the CAR, however, evidence of only three of these HBV genotypes (A, D and E) were reported in previous studies [15,21,28,29].…”
Section: Plos Onementioning
confidence: 97%